Authenticity Is in the Eye of the Beholder: The Exploration of Audiences' Lay Associations to Authenticity Across Five Domains. Issue 1 (March 2019) - Kovács, Balázs
Existing research has proposed multiple definitions to authenticity. Instead of such a definitional approach, this article takes a bottom-up approach and provides an exploratory assessment of lay associations to authenticity. I conducted a survey that asked participants to list the words they associate with authentic restaurants, people, paintings, brands, and organizations. I find that there is substantial variance among individuals in their associations to authenticity, and the meanings they evoke also change with the domain of evaluation. People also vary in the level of importance they place on authenticity across the different domains. I discuss the implications of these findings for authenticity research and practice in psychology, marketing, management, and sociology.